Automating the mixing and spraying stage of the instant mashed potato process - Palacios Huaraca, Carlos Rubén (2021)
The article describes a control logic used to automate the mixing stage of the instant mashed potato process, in order to improve the quality of the final product. Thus, initially the characteristics of the automated process are detailed, specifying the programming logic on the programmable logic controller, to later demonstrate through a data collection process the percentage of improvement in the quality of the final product from the perspective of the users. Indicators: percentage of humidity in the mixing stage, water absorption index (IAA), water solubility index (ISA) and hydrogen potential (pH). The development of the research concludes that the automation of the process, achieved that the IAA index and the ISA index, obtained in the spraying stage, improve by 8.13% and 23.05%, respectively, finding analyzed values within the optimal ranges. This in turn reflected a 39.61% improvement with respect to the humidity percentage, measured in the mixing stage, thus improving the quality of the final product, which brings with it a significant increase of 84.44% in production levels.